Analisis Fungsi Faal Paru dan Faktor-Faktor yang Mempengaruhi Terhadap Terkontrol Tidaknya Asma - Pratiwi, Rahmifah Putri (Yayasan Citra Cendekia Celebes, 2023)
Asthma is one of the most prevalent diseases, morbidity, and mortality in the world. Asthma can arise at any age, whether male or female. Asthma is an intermittent, reversible obstructive airway disease in which the trachea and bronchi respond in hyperactivity to a particular stimuly. The aim of this research is to know the difference of proportion of lung function in fully controlled and uncontrolled asthma based on Asthma Control Test (ACT) criteria. This research is an observational analytic research that looking for relationship between variable X and variable Y through hypothesis testing with cross sectional approach. A sample of 17 people with asthma. Population selection based on the diagnosis of asthma diagnosed by a lung specialist. Of the selected populations that meet the inclusion and exclusion criteria. Samples are assessed for their asthma control level based on the Asthma Control Test (ACT) criteria. Data analysis was performed using Statistical Program for Social Sciences (SPSS), ie univariate and bivariate analysis. The results showed no association between controlled asthma based on ACT with age and gender. There was a relationship between ACT-based controlled asthma and education level where p = 0.022 (P <0.05) and had a strong correlation for low and moderate low-level education level categories. While the correlation is sufficient for medium category with high. There was a relationship between ACT-based asthma-controlled asthma and the degree of asthma where p = 0.022 (P <0.05) and had a strong correlation for mild degrees of severe severe and moderate degrees of asthma. Whereas the correlation is sufficient for the light weight category